Components of slow rusting mechanism and integrated management of pearl millet rust in Karnataka, India - HANAMANTH, P.V. PATIL*, H. NAGARAJA and (Indian Phytopathology, 2016)
Rust caused by Puccinia substriata Ell. and Barth. var. indica Ramachar and Cummins is one of the major diseases affecting both forage and grain production in pearl millet.It is reported to cause up to 48.81 per cent reduction in grain yield in highly rust susceptible pearl millet genotype, GHB 558. Five components of slow rusting mechanism viz., latent period, uredial density, uredial size, apparent infection rate(r) and area under disease progress curve (AUDPC) were studied in nine pearl millet genotypes for assessing the nature of slow rusting or partial resistance. Pearl millet genotypes, J 2496 (2786.70), J 2510 (3240.30), J 2517 (3175.55) and 70 SB 13 (3175.55) recorded lower values for AUDPC and increased latent period (11-12days) and decreased uredial density (5.25/cm2 to 6.16/cm2) and hence are categorized as slow rusters. In vitro evaluation of fungicides, commercially available botanicals and indigenous technology knowledge (ITKâ€™s)by â€œcavity slideâ€ method indicated thathexaconazole, propiconazole and triadimefonamong systemic fungicides at 0.075 and 0.1 per cent, mancozeb and chlorothalonil among non systemic fungicides at 0.1 and 0.2 per cent, neem oil and soldier among commercially available botanicals at 0.75 and 1.00 per cent, cow urine and cow milk among ITKâ€™s at 20 and 30 per cent concentrations inhibited maximum uredospore germination of P. substriata var. indica. Among the different spray schedules evaluated under field condition, hexaconazole @ 0.1% followed by hexaconazole @ 0.1% spray schedule recorded least rust severity (15.30%), highest seed yield (30.50 q ha-1) and 1000 seed weight (10.51 g) withhighest benefit : cost ratio of 2.40.